About the problems and results of obtaining products from technical ceramics for metallurgical production. Message 1 - F. I. Panteleenko; R. Yu. Popov; V. T. Shmuradko; A. S. Samsonova (Литьë и металлургия, 2023)
The article presents the research’s results in the field of multifunctional ceramic materials synthesis for metallurgical, machine‑tool and other branches related to the metal treatment, their alloys and products from them; current trends and tendencies associated with the production of goods from such materials. The information on expanding the local raw material sources for the production of ceramics with the involvement of local enterprises is provided. In addition, the prospects for the industrial potential development to produce such goods are observed.